A systematic literature review on the attributes and profusion of microplastic in marine and river fish around Southeast Asian waters / Siti Nurshafiqah Ahmad Husaini - Ahmad Husaini, Siti Nurshafiqah (2022)
Microplastics are tiny pieces of plastic smaller than five millimeters in size that have been identified as major pollutants in aquatic ecosystems. The abundance of microplastics poses severe threats to aquatic species globally in recent years. Microplastic ingestion in different marine species has been widely observed throughout the previous decade. Meanwhile, the consumption of marine and river fish is prevalent across Southeast Asian countries where the microplastics pollution can become an issue. This study is aimed to investigate the attributes and profusion of microplastic in marine and river fish around Southeast Asian waters using a systematic literature review technique. From the analysis, it was found that most of the studies classified microplastics according to their types, colors, and abundance. Microplastic fragment was the dominant type found in both marine and river fish around Southeast Asian waters. The dominant microplastic color in both marine and river fish was blue. Moreover, the abundance of microplastics in marine fish is higher than river fish. Further study is required to have a better knowledge and analyze the risks associated with marine and river food safety across Southeast Asian waters.